2019
DOI: 10.1177/1741134319875764
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice among pharmacy professionals towards generic medicines in Addis Ababa, Ethiopia

Abstract: Background: Suboptimal knowledge and attitude of healthcare professionals about generics reduce utilization of these drugs. The objective of this study was to assess the knowledge gap, attitude and practice among pharmacy professionals toward generic medicine in Addis Ababa, Ethiopia. Method: The study was conducted in Addis Ababa from 10 April to10 July 2018 among 424 pharmacy professionals. Self-administered questionnaire was used to collect the data. Data were analyzed by using statistical package for socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 17 publications
8
8
3
Order By: Relevance
“…This is consistent with the findings of a study carried out in Addis Ababa, Ethiopia. 17 but was at variance with the findings from studies carried out in Qatar, Poland, Palestine and Saudi Arabia where participants' demographic characteristics had nothing to do with their knowledge of generic medicines. 14,16,40,41 A result which suggests that the observed differences may be attributed to variances in country's laws and policies about generic medicines.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…This is consistent with the findings of a study carried out in Addis Ababa, Ethiopia. 17 but was at variance with the findings from studies carried out in Qatar, Poland, Palestine and Saudi Arabia where participants' demographic characteristics had nothing to do with their knowledge of generic medicines. 14,16,40,41 A result which suggests that the observed differences may be attributed to variances in country's laws and policies about generic medicines.…”
Section: Discussioncontrasting
confidence: 81%
“…The results obtained about knowledge of generic medicines in our study, are consistent with the results from similar studies carried out in Saudi Arabia, Ethiopia and India. 15,17,39 Our result further showed that the knowledge of community pharmacists was significantly associated with demographic characteristics of the respondents such as gender, age, work experience and country of graduation. This is consistent with the findings of a study carried out in Addis Ababa, Ethiopia.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Generic substitution (GS) refers to a substitution of a prescribed brand medicine by a different form of an identical active substance or switching from prescribed brand medicines to identical generic medicines [ 6 , 12 ]. The practice of GS is strongly supported by health authorities globally [ 13 ]. GS can improve medicines utilization by making it more accessible and affordable [ 1 ].…”
Section: Introductionmentioning
confidence: 99%